QUALITY OF ECONOMIC EDUCATION IN HIGHER EDUCATIONAL INSTITUTIONS - WAYS TO REFORM THE TEACHING SYSTEM - Khudoynazar Ergashev; Farruxxon Marupov (Western European Studies, 2023)
The topic of economic education was, is and will be relevant at all times, because it concerns everyone, the individual, and the planet as a whole. At the end of the 20th century, our country began the transition to a market economy, a market economic mechanism. By saying goodbye to the administrative-command system in the economy and society, we thereby destroy the usual stereotypes of perceiving the world, and there is a deep rethinking of basic, conceptual actions in the theory of public education. The purpose of this article is to review and analyze the degree and level of economic education in universities today and compare what has been studied with the quality of teaching economic education in the “past”, or more precisely at the end of the 19th century and the beginning of the 21st century.
Keywords: higher economic education; secondary education; elementary fundamentals